Study of Magnetic Shielding in Conductors Materials as a Function of the Frequency. - Torres Velásquez, J. A.; Viáfara Avila, R. R.; Chacón Cardona, C. A. (Universidad Pedagógica y Tecnológica de Colombia, 2016)
This study describes the effect of a uniform magnetic field in conductive materials, and how they shieldthe magnetic field that travel through them. In order to create such a field, two coilis are energized by a sinusoidal signal produced by a signal generator with a difference of potential of 10 [Vp]. The magnetic field measurement is performed indirectly by placing a coil as a sensor in the center of a larger diameter coil, performing the tension difference of potential measurement on the sensor,in such way that by placing a shielding material that encloses the coil and its sensor, the magnetic field inside is reduced, therefore also diminishes the induced tension in the coil. The shielding materials used were steel, aluminum, iron and copper, the efficiency of these materials was studied in a frequency range from 60 to 100.000 Hz, resulting that iron is more efficient than the others from 60 to 12.000 Hz, and for 32.000-100.000 Hz the best shielding material, was copper.